Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12876-017-0651-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of heme oxygenase-1 against severe acute pancreatitis via inhibition of tumor necrosis factor-α and augmentation of interleukin-10

Abstract: BackgroundHeme oxygenase-1 (HO-1) is an inducible defense gene which plays a significant role in inflammation. HO-1 protects cells and tissues through the mechanism of anti-oxidation, maintaining microcirculation and anti-inflammation. The aim of the current study is to investigate the role of HO-1 on systemic inflammatory response in severe acute pancreatitis (SAP).MethodsForty male Sprague-Dawley (SD) rats were randomly assigned into four groups: control group (n = 10); SAP group (n = 10), SAP model was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 39 publications
(46 reference statements)
1
36
0
2
Order By: Relevance
“…Previous studies indicated that HO-1, which protects cells and organs against inflammation-induced injury and oxidative stress, plays an essential role in SAP pathogenesis including many other inflammatory disorders associated with the immune system [35][36][37][38][39]. This study revealed that HO-1 induction during the early stages of SAP development modulated systemic inflammatory response through TNF-α suppression and IL-10 augmentation [20].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Previous studies indicated that HO-1, which protects cells and organs against inflammation-induced injury and oxidative stress, plays an essential role in SAP pathogenesis including many other inflammatory disorders associated with the immune system [35][36][37][38][39]. This study revealed that HO-1 induction during the early stages of SAP development modulated systemic inflammatory response through TNF-α suppression and IL-10 augmentation [20].…”
Section: Discussionmentioning
confidence: 61%
“…The rats were grouped into four categories (n = 10): SAP group, sham surgery (SS) group, SAP + SMI group, SAP + SMI + Zinc protoporphyrin (ZnPP) group, a specific inhibitor of HO-1 [19]. The SAP model was designed by retrogradely injecting the rats with 4% sodium taurocholate (1 ml/kg) via the pancreatic duct following anaesthetization with sodium pentobarbital (40 mg/kg) [20]. The SAP group rats were intravenously injected with 1.6 ml/kg saline 30 minutes after induction of SAP.…”
Section: Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Shenmai injection (SMI) is a traditional Chinese medicine comprising Ophiopogonjaponicas (lilia-ceae), and Ginseng Rubra (araliaceae) extracts [18] and is widely used to clinically treat heart diseases, sepsis, osteoarthritis and asthma [19][20][21][22]. SMI is generally considered a safe drug [23,24].…”
Section: Introductionmentioning
confidence: 99%